2016
DOI: 10.1209/0295-5075/113/27004
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to normalize Compton profiles of pure incoherent scatterers

Abstract: -In this paper we show that the effective atomic number of amorphous materials which can be treated as pure incoherent scatterers can itself be used as a constant for normalizing the experimental Compton profiles. This finding is expected to be useful since calculation of the normalization constant by the usual procedure of integrating the Biggs et al. Compton profile values is a tedious task for composite materials. This method is applicable to pure incoherent scatterers of known as well as unknown compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Later in 1998, Kahane [20] provided a relation between the normalization constant obtained from integrating the Compton profile with that of the incoherent scattering function S(q, Z). In our recent paper in EPL [21] we have shown that this constant itself is Z eff for pure incoherent scatterers and an experimental support for this has been provided in another paper recently published by us elsewhere [22]. This would in fact pave a way towards interpreting Z eff through a fundamental theoretical basis.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Later in 1998, Kahane [20] provided a relation between the normalization constant obtained from integrating the Compton profile with that of the incoherent scattering function S(q, Z). In our recent paper in EPL [21] we have shown that this constant itself is Z eff for pure incoherent scatterers and an experimental support for this has been provided in another paper recently published by us elsewhere [22]. This would in fact pave a way towards interpreting Z eff through a fundamental theoretical basis.…”
supporting
confidence: 58%
“…It is known that [4,21,24] for pure incoherent scatterers the incoherent scattering function is nothing but Z eff , i.e., S(q, Z) = Z eff .…”
Section: S(q Z)mentioning
confidence: 99%
“…Algorithm of our approach to determine the normalized Compton profile [13] demands the determination of SDCS as the first step. So, SDCS values have been measured for 241 Am gamma rays at a scattering angle 120 • using a goniometer assembly with a collimator type geometry.…”
Section: Methodsmentioning
confidence: 99%
“…The K shell binding energy of the constituent elements ples is as given in Table 1. It can be noticed from the table that the Compton shift far exceeds the binding energy of the constituent elements of the stone samples so that these samples can be considered to be pure incoherent scatterers [13,22]. Hence, the normalized Biggs et al Compton profile [15] of each relavant orbital of the constituent element of the stone samples of interest was calculated and these values have been combined using mixture rule [16].…”
Section: Normalization Of Compton Profiles With Z Effmentioning
confidence: 99%
See 1 more Smart Citation